Isoniazid preventive therapy use among adult people living with HIV in Zimbabwe. (October 2021) - Takamiya, Mayuko; Takarinda, Kudawashe; Balachandra, Shrish; Godfrey, Musuka; Radin, Elizabeth; Hakim, Avi; Pearson, Michelle L; Choto, Regis; Sandy, Charles; Maphosa, Talent; Rogers, John H
We assessed the prevalence of isoniazid preventive therapy (IPT) uptake and explored factors associated with IPT non-uptake among people living with HIV (PLHIV) using nationally representative data from the Zimbabwe Population-based HIV Impact Assessment (ZIMPHIA) 2015–2016. This was a cross-sectional study of 3418 PLHIV ZIMPHIA participants eligible for IPT, aged ≥15 years and in HIV care. Logistic regression modeling was performed to assess factors associated with self-reported IPT uptake. All analyses accounted for multistage survey design. IPT uptake among PLHIV was 12.7% (95% confidence interval (CI): 11.4–14.1). After adjusting for sex, age, rural/urban residence, TB screening at the last clinic visit, and hazardous alcohol use, rural residence was the strongest factor associated with IPT non-uptake (adjusted OR (aOR): 2.39, 95% CI: 1.82–3.12). Isoniazid preventive therapy non-uptake having significant associations with no TB screening at the last HIV care (aOR: 2.07, 95% CI: 1.54–2.78) and with hazardous alcohol use only in urban areas (aOR: 10.74, 95% CI: 3.60–32.0) might suggest suboptimal IPT eligibility screening regardless of residence, but more so in rural areas. Self-reported IPT use among PLHIV in Zimbabwe was low, 2 years after beginning national scale-up. This shows the importance of good TB screening procedures for successful IPT implementation.